Strange Things Are Happening: Reaching for the Retro in Response to Contemporary Crisis. - Garas, Julia (Limina, 2025)
The article examines how the television series *Stranger Things* reflects a contemporary identity crisis through its nostalgic representation of the 1980s. It argues that the series evokes a longing for the past as a means of coping with present uncertainties, utilizing cultural artifacts and aesthetics that resonate with viewers. The concept of "prosthetic memory," as proposed by Alison Landsberg, is discussed to illustrate how collective memory is shaped by media, allowing audiences to connect with a shared past. Ultimately, *Stranger Things* serves as a cultural touchstone that fosters a sense of belonging and continuity amid the complexities of modern life, while also selectively interpreting the historical context of the 1980s.